Self-assembly of a cyclic Zn4O4 tetramer by aerobic oxidation of a bisoxazoline: a molecular "Nest" for nucleophilic OH- - Jacques, Béatrice; Dro, Clémence; Bellemin-Laponnaz, Stéphane; Wadepohl, Hubert; Gade, Lutz H. (Angewandte Chemie. International edition, 2008)
Nesting hydroxide: Coordination and aerobic oxidation of a bisoxazoline Me2box is coupled with self-assembly to form a highly ordered [(Me2box)O4Zn4]4+ complex. The metallamacrocycle acts as a nest-like hydroxide receptor (see scheme, right) and shows catalytic phosphatase activity.